DISCIPLINE PROGRAM FOR IMPROVING STUDENT LEARNING OUTCOMES AT TSANAWIYAH MADRASAH KANJENG SEPUH, SIDAYU, GRESIK - Moh. Hasyim Rosyidi; Muhammad Haris; Farotin Farotin (at-Tahsin, 2022)
MTs Kanjeng Sepuh is one of the educational institutions that was established under the auspices of the Taman Pendidikan Kanjeng Sepuh foundation which has a discipline program through two attendance systems (paper absent and fingerprint absent) which have been implemented simultaneously since 2014 which are closely monitored by picket teachers and other supervisory teachers. This program is able to help improve student learning outcomes because the teaching and learning process is more focused and more conducive. This researcher aims to answer some problem formulations; 1). How is the discipline program in improving student learning outcomes at MTs Kanjeng Sepuh, Sidayu sub-district, Gresik district? 2). What are the supporting and inhibiting factors in implementing discipline programs in improving student learning outcomes at MTs Kanjeng Sepuh, Sidayu sub-district, Gresik district. This type of research includes qualitative research, which produces data and is analyzed using descriptive methods adapted to the disciplinary program in improving student learning outcomes at MTs Kanjeng Sepuh Sidayu Gresik. The results of this study, that MTs Kanjeng Sepuh in implementing the student attendance disciplinary program uses a 2 attendance system, namely manual attendance which is carried out in class (paper attendance) and non-manual attendance (fingerprint) simultaneously and the program runs effectively as evidenced by the persistence of the program from year after year, positive responses from related parties to the implementation of the program and getting maximum learning outcomes are evidenced by student achievements every year. As for the implementation of the program, of course there are supporting factors and inhibiting factors, this is the supporting factor of the effectiveness of the discipline program in improving student learning outcomes at MTs Kanjeng Sepuh as follows: 1). Response or cooperation of all related parties, 2). Achievement targets that meet, 3). Adequate facilities, 4) make it easy to recap data, 5). Has 2 attendance data to be more accurate. As for the inhibiting factors of the effectiveness of the discipline program in improving student learning outcomes at MTs Kanjeng Sepuh as follows: 1). Uncertain internet connection (fingerprint attendance), 2). The electricity goes out and the pulse runs out without being caught (fingerprint attendance), 3). Lost files (manual attendance), 4). Requires a large budget (manual attendance), 5). Queues to queue for fingerprint attendance are boring.